2023
DOI: 10.1590/1806-9282.20230533
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of age, creatinine, and left ventricular ejection fraction risk score in patients evaluated with fractional flow reserve: a cross-sectional study

Adem Aktan,
Tuncay Güzel

Abstract: SUMMARY OBJECTIVE: In this study, we investigated the relationship between age, creatinine, and left ventricular ejection fraction risk score and the severity of coronary lesions detected by applying fractional flow reserve in the patient group presenting with chronic coronary syndrome. Also, we presented long-term follow-up results in patients whose age, creatinine, and left ventricular ejection fraction score was evaluated by the fractional flow reserve procedure. MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, acute kidney injury (AKI) after PCI is associated with an increase in mortality [ 2 , 3 ], and Murata et al also reported that persistent worsening renal function (WRF) is associated with a high incidence of all-cause mortality and major adverse cardiac events in patients who underwent PCI for acute coronary syndrome [ 4 ]. Moreover, chronic kidney disease (CKD) is an independent risk factor for cardiovascular events and all-cause mortality, predicting cardiovascular events as effectively as other established risk factors [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, acute kidney injury (AKI) after PCI is associated with an increase in mortality [ 2 , 3 ], and Murata et al also reported that persistent worsening renal function (WRF) is associated with a high incidence of all-cause mortality and major adverse cardiac events in patients who underwent PCI for acute coronary syndrome [ 4 ]. Moreover, chronic kidney disease (CKD) is an independent risk factor for cardiovascular events and all-cause mortality, predicting cardiovascular events as effectively as other established risk factors [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%